Differences in the Effect of Small Sided Game and Drill Training Methods on Passing Accuracy and V02Max in Football Games in High School Students - Muhammad Asrul; Tarsyad Nugraha; Indra Kasih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the difference in the effect of small sided games and drill on passing accuracy and VO2Max in soccer games. This research is using experimental method. The sample in this study is 26 people, then divided into two groups using matching by fairing techniques. The results of this study, namely the first hypothesis obtained t-hit of 6.96 and t-table 1.78, then (6.96> 1.78) Ha is accepted and Ho is rejected. The second hypothesis is obtained t-hit of 4.98 and t-table 1.78, then (4.98> 1.78) Ha is accepted and Ho is rejected. The third hypothesis is obtained t-hit of 13.01 and t-table 1.78, then (13.01> 1.78) Ha is accepted and Ho is rejected. The fourth hypothesis is obtained t-hit of 5.79 and t-table 1.78, then (5.79> 1.78) Ha is accepted and Ho is rejected. The fifth hypothesis is obtained t-count 3.063 and t-table 1.71 (3.063> 1.71) and (0.005 <0.05) then Ha is accepted and Ho is rejected. The sixth hypothesis is obtained t-count 3,971 and t-table 1,71 (3,063> 1,71) and (0,001 <0,05) then Ha is accepted and Ho is rejected. The conclusion of this study is, There is a significant effect of the small sided games training method on improving passing accuracy. There is a significant effect of the drill training method on increasing passing accuracy. There is a significant effect of the small sided games training method on increasing VO2max. There is a significant effect of the drill training method on increasing VO2max. There is a significant difference in the effect of the small sided games training method with the drill on improving soccer passing accuracy. There is a significant difference in the effect of the small sided games training method and the drill training method on increasing VO2Max.